1751 Influenza vaccination uptake in healthcare workers in ireland: effectiveness of a brief educational intervention in promoting positive attitudinal change. (24th April 2018) - McNally, Grainne; McDonnell, Conor; Tobin, Laura
Abstract : Introduction: Annual Influenza vaccination rates among Healthcare Workers (HCW) in Ireland are almost universally low despite national and international recommendations. Improving HCW Influenza vaccination rates remains an annual challenge for Occupational Health Departments. Previously studied intervention strategies that increased vaccine uptake internationally include: provision of free vaccine, easy access to the vaccine, knowledge and behaviour modification through educational activities and/or reminders and/or incentives. The aim of this study was to determine if attitudes towards the Influenza vaccination in HCW in Ireland remained a barrier to uptake of vaccination and if a brief educational intervention could cause an attitudinal shift towards receiving the vaccination. It also questioned the attitudes of HCW towards mandatory Influenza vaccination. Methods: A brief interventional video was commissioned locally prior to the start of the national influenza campaign 2017/18. It contained local healthcare staff discussing evidence based facts regarding the influenza vaccination and rationale for HCW uptake. HCW who attended the intervention were offered a questionnaire at the educational session assessing their attitude towards the vaccination. Result: 157 HCW attended and 143 completed the questionnaire. In 2016/17 Influenza season 43.4% (n=62) indicated they received the influenza vaccination. Following the intervention, the intention to receive the vaccination in 2017/18 increased to 76.2% (n=109). A further 15.3%(n=22) indicated vaccination consideration. 50.3% (n=72) stated the brief intervention had influenced their decision. Prior to the educational intervention 39.2% (n=56) agreed with mandatory Influenza vaccination for HCW. This increased to 49.7% (n=71) post intervention. Discussion: The brief educational intervention increased the numbers of HCW indicating they would get or would consider getting the annual Influenza vaccination. The intervention was noted as an influencing factor and could be a useful tool in increasing the vaccination rate amongst HCW in Ireland particularly if engagement with it was a mandatory requirement.